Mediator Analysis of Perceived Organizational Support: Role of Spiritual Leadership on Affective Commitment - Rumangkit, Stefanus (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2020)
This study aims to investigate the influence of spiritual leadership and perceived organizational support on affective commitment. In addition, the moderating role of perceived organizational support in the relationship of spiritual leadership and affective commitment will be tested. This research was conducted with survey research design, and the type of data was cross-sectional. Surveys conducted based on web based surveys. Research focuses on organizational members or employees in the Bandar Lampung region. Data is collected by self-administered survey with sampling in the form of non-probability sampling, namely by purposive sampling. Processing data and testing hypotheses is done using moderated regression analysis. The number of respondents in this study amounted to 130 respondents. Spiritual leadership is measured by SLT survey questions developed by Fry et al (2005), with 17 items of questions. Affective commitment was measured by 6 items of measurement scale developed by Meyer, Allen and Smith (1993). Whereas, perceived organizational support was measured by the short version of (Eisenberger et al., 1986), consisting of 8 statements.The results of the investigation show that spiritual leadership and perceived organizational support influence affective commitment. In particular, the moderating effect of perceived organizational support can strengthen the relationship of spiritual leadership and affective commitment.